Pelatihan Perancangan dan Pengaplikasian Alat INTENSOR - M. Dewi Manikta Puspitasari; Miftakhul Maulidina; Agus Suwardono; Elsanda Merita Indrawati; Kartika Rahayu Tri P. S (Yayasan Literasi Sains Indonesia, 2023)
Technological developments have a role in the competition for metal processing in the home industry, namely the development of metal heating devices. However, the home industry needs to consider environmentally friendly metal heaters. One of the environmentally friendly metal heaters is an induction heater. Induction heater has a metal heating technique by utilizing electromagnetic induction which is more efficient than using a conventional metal heating furnace. Induction heaters have advantages in terms of easier use, efficient in terms of energy, time and temperature regulation. Induction heating is a metal heating technique by utilizing electromagnetic induction from high frequency AC waves, which is more efficient than using conventional metal heating furnaces. This problem is the basis for holding training on the design and application of the INTENSOR tool. This community service activity has had quite a good impact in: 1) increasing the knowledge and skills of metal processing business actors in designing INTENSOR tools; 2) increase the knowledge of metal processing business actors in making and applying INTENSOR tools. Community service activities are carried out for 6 months and are intended for metal processing business actors.